2021
DOI: 10.3390/pathogens10101295
|View full text |Cite
|
Sign up to set email alerts
|

Sea Turtles in the Cancer Risk Landscape: A Global Meta-Analysis of Fibropapillomatosis Prevalence and Associated Risk Factors

Abstract: Several cancer risk factors (exposure to ultraviolet-B, pollution, toxins and pathogens) have been identified for wildlife, to form a “cancer risk landscape.” However, information remains limited on how the spatiotemporal variability of these factors impacts the prevalence of cancer in wildlife. Here, we evaluated the cancer risk landscape at 49 foraging sites of the globally distributed green turtle (Chelonia mydas), a species affected by fibropapillomatosis, by integrating data from a global meta-analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 127 publications
0
24
0
Order By: Relevance
“…Herpesviruses are horizontally transmitted from one infected host to another by bodily fluid such as saliva, mucus, or direct physical contact [15,22]. Horizontal transmission of ChHV5 has been reported to occur through viral particle shredding in the water [36,37]. The dispersal and virulence of the viral particle are influenced by the water temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herpesviruses are horizontally transmitted from one infected host to another by bodily fluid such as saliva, mucus, or direct physical contact [15,22]. Horizontal transmission of ChHV5 has been reported to occur through viral particle shredding in the water [36,37]. The dispersal and virulence of the viral particle are influenced by the water temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The dispersal and virulence of the viral particle are influenced by the water temperature. It was reported that herpesvirus remains infectious at 23-30 • C as higher temperatures are documented to enhance herpesviruses replication [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…Human activities are increasingly degrading the environment, often creating evolutionary mismatches between the risk of developing malignancies and the effectiveness of natural cancer defences [1]. As a result, many wildlife species are now developing cancers [2][3][4][5][6]. Because of the exacerbated need to activate anti-cancer defences [7], and/or because of the adverse effects of the disease itself [8], many phenotypic traits are substantially altered in these individuals, which may even ultimately influence ecosystem functioning [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a characteristic shared by virtually all zoo animals is that they are, for a variety of reasons, cleared of a fraction of their parasitic load (Hosey et al, 2009). This provides a unique experimental context for exploring the hygiene hypothesis of pathologies, including cancer (Dujon, Schofield, et al, 2021). Several mechanisms suggest infections by parasites may offer protection from cancer in mammals.…”
Section: Introductionmentioning
confidence: 99%